The Influence Of Problem Based Learning Strategy With Basic Calculus Approach - Simangunsong, Sumihar; Parsaoran, Dede (Universitas PGRI Sumatera Barat, 2021)
This research was motivated by the low learning outcomes of students in basic physics courses. The purpose of this study was to analyze high learning outcomes as a result of the application of problem-based learning with a basic calculus approach.The samples of this study were students majoring in mining ISTP Medan and students majoring in physics, University of North Sumatra, TA 2019/2020 academic year, totaling 35 people as one sample group. Thi research is a Quasi-experimental one group design. The technique in analyzing the pretest and posttest data is the analysis of the gain value (Gain Score). To see the learning outcomes, a learning outcome test is used and a gain test is used to improve learning outcomes. The results showed that there was an increase in gain at each high meeting, it was concluded that the benefits of problem-based learning strategies with the basic calculus approach could increase student learning outcomes. The implication of this research resulted in a strong stimulus to make basic physics teaching materials using the basic calculus approach even greater and more positive.